The Influence of Leadership Style and Work Environment on Motivation and Its Implications on Performance PT. Nuansa Citramandiri - Syapril Janizar; Deden Komar Priatna; Winna Roswinna; An An Anisarida; Maria Lusiana Yulianti (Greenation Research & Yayasan Global Resarch National, 2023)
Employees are human resources that are very important for the company because they have the mind, mind, talent, creativity, and energy needed to do all the work given by the company to achieve company goals. The better the performance of individuals within a company, the better the performance of the company, and vice versa, the lower the performance of individual employees will reduce the performance of the company. The research aims to examine and analyze the effect of leadership style and work environment on work motivation and performance at PT. Nuansa Citramandiri both simultaneously and partially. The analytical method used in this research is path analysis schematic diagram of the two sub-structures so that the research is descriptive and verificative, namely collecting, presenting, analyzing and testing hypotheses to get conclusions and suggestions using Statistical Product and Service Solution (SPSS). The research was conducted at a consulting service company, PT. Nuansa Citramandiri with a research sample of 97 respondents. The research data were obtained from a 5-point ordinal scale questionnaire which was transformed into interval data. The results of the study are: 1) There is a partial influence of leadership style on employee motivation at PT. Nuansa Citramandiri; 2) There is a partial influence of the work environment on employee motivation at PT. Nuansa Citramandiri; 3) There is an influence of leadership style and work environment simultaneously on motivation at PT. Nuansa Citramandiri. 4) There is an influence of work motivation on performance at PT. Nuansa Citramandiri.